MARKETING MIX STRATEGY OF SERVICES AND ITS INFLUENCE ON PATIENT DECISIONS IN CHOOSING A HOSPITAL - Widiastuti, Tri Marhaeni; Kumalasari, Klara; Andriani, Riza (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose : This study aims to determine the effect of the 7p service marketing mix strategy which includes product, price, promotion, place, people, process, and physical evidence, on patient decisions in choosing a hospital. Design/methodology/approach: the appropriate type of research is explanatory and the approach used is quantitative. The number of samples is 100 people, namely some inpatients at Hospital X, with the Accidental Sampling technique. Data were collected by means of observation and distribution of questionnaires and analyzed using multiple linear regression inferential statistical analysis, and assisted by SPSS version 2023 application processing media. Finding: The results obtained are that product, price, promotion, people, process, and physical evidence have a significant effect on patient decisions in choosing a hospital, while place has no significant effect. Practical implications: this study suggests that hospitals add service products (home care services), provide larger parking spaces and be located in the hospital environment because parking is one of the physical evidence considered by patients/visitors to choose a hospital Originality: this study found that place has no significant effect on patient decisions in choosing Hospital X, possibly because this hospital is a special hospital, so patients ignore the less strategic location of the hospital as a consideration in decision making Paper type: research paper